2019
DOI: 10.1021/acsapm.9b00685
|View full text |Cite
|
Sign up to set email alerts
|

Wire Melt Electrospun Polymer Nanocomposite Fibers as Radio Frequency Responsive Heaters

Abstract: We have demonstrated noncontact heating of melt electrospun polymer fibers by using radio-frequency (RF) fields which heat carbon nanotube (CNT) receptors inside the fibers. RF radiation is attractive as it allows for noncontact heating of polymers with low concentrations of CNTs. We observed that the heating rate scales with the CNT loading even below the bulk electrical percolation threshold, suggesting that individual CNTs can serve as RF receptors/heat sources. This capability eliminates the requirement fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Non-contact heating of melt electrospun polymer bers embedded with CNTs can be achieved by using RF elds for applications such as plastic electric heaters, hyperthermia treatment, and heat-generating textiles. 41 For medical applications, RF plasma can be used for sterilization of surgical and dental devices to eradicate cellulose and bacterial spores, 42,43 and other contaminants; 44 furthermore, dental devices can also be sterilized by RF elds. 45 Additionally, RF elds can be used for hyperthermia and drug release, [46][47][48] and non-invasive body fat reduction.…”
Section: Minireview Nanoscale Advancesmentioning
confidence: 99%
“…Non-contact heating of melt electrospun polymer bers embedded with CNTs can be achieved by using RF elds for applications such as plastic electric heaters, hyperthermia treatment, and heat-generating textiles. 41 For medical applications, RF plasma can be used for sterilization of surgical and dental devices to eradicate cellulose and bacterial spores, 42,43 and other contaminants; 44 furthermore, dental devices can also be sterilized by RF elds. 45 Additionally, RF elds can be used for hyperthermia and drug release, [46][47][48] and non-invasive body fat reduction.…”
Section: Minireview Nanoscale Advancesmentioning
confidence: 99%
“…44 Carbon nanotubes, for instance, have been studied as conductive filler for polymers in fibers and for additive manufacturing to induce noncontact heating by electromagnetic waves. 45,46 This research focused on a first investigation of material-process interactions during the novel manufacturing technology of radiofrequency welding of bead foams. This required a detailed analysis of the dielectric properties of polybutylene terephthalate (PBT) as bulk polymer and in the form of foam beads by specialized measuring cells.…”
Section: Introductionmentioning
confidence: 99%
“…For bead foams based on unpolar polymers like expanded polypropylene (EPP) additional polar substances need to be added within the polymer matrix as fillers or coated on the surface of the particles to induce heating and subsequent welding 44 . Carbon nanotubes, for instance, have been studied as conductive filler for polymers in fibers and for additive manufacturing to induce noncontact heating by electromagnetic waves 45,46 …”
Section: Introductionmentioning
confidence: 99%
“…RF heating also allows continuous processing; Vashisth et al have shown an RF scanning approach to process C-fiber and epoxy prepregs in a continuous and oven-free approach . Morikawa et al utilized inside-out RF heating to melt the core of CNT–poly­(ε-caprolactone) fibers, while the temperature of the surface is still 10–15 °C lower without deforming the shape of fibers …”
Section: Introductionmentioning
confidence: 99%